2015
DOI: 10.1590/0103-6440201300111
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implants: Alternative for Oral Rehabilitation of a Child with Ectodermal Dysplasia

Abstract: Ectodermal dysplasia is a rare congenital disease that affects several structures of ectodermal origin. The most commonly related oral characteristics are hypodontia, malformed teeth and underdeveloped alveolar ridges. New alternative treatments are needed due to the failure of the conventional prosthesis retention. This case report outlines the oral rehabilitation treatment of a 9-year-old girl with ectodermal dysplasia. The treatment was performed with conventional prosthesis upon mini-implants. The mini-imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Although, in general, dental implant placement is contraindicated in the growing jaw, children with severe oligodontia or anodontia may benefit from implants placed in selected regions; an improvement of denture retention may enhance both craniofacial and psychosocial development . The use of mini‐implants was described in four publications . With regard to their advantages ‐ reduced diameter, small surgical insertion protocol, no need for submerged healing, immediate prosthetic restoration, small costs ‐ they should be considered as feasible provisional solution until the completion of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in general, dental implant placement is contraindicated in the growing jaw, children with severe oligodontia or anodontia may benefit from implants placed in selected regions; an improvement of denture retention may enhance both craniofacial and psychosocial development . The use of mini‐implants was described in four publications . With regard to their advantages ‐ reduced diameter, small surgical insertion protocol, no need for submerged healing, immediate prosthetic restoration, small costs ‐ they should be considered as feasible provisional solution until the completion of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen case reports, 16,18,19,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] five case series, 21,24,44,46,63 and one cohort study 26 reported on prosthetic rehabilitation of 39 children TA B L E 2 (Continued) (33 males, six females) with HED at ground school age ( Table 2). One individual was described twice, 63,64 but is only included once in our analysis.…”
Section: Kids Mixed Dentitionmentioning
confidence: 99%
“…Psychological wellbeing and good nutrition are the most important reasons for placing an implant in a growing individual. In addition, excellent blood supply and good bone healing lead to increased stability and retention of prosthetic rehabilitation in patients during the growth phase 13,19) . Maxillary development occurs through apposition and surface remodeling 6) , with the latter taking place as growth proceeds downward and forward in relation to the cranium and base of the skull.…”
Section: Discussionmentioning
confidence: 99%
“…Mello [27] 2015 Retrospective The patient adapted very well with the dental prosthesis. She showed great satisfaction with an increase in self-esteem and an improvement in her social skills.…”
Section: Discussionmentioning
confidence: 99%
“…Though there were reports of implant failure on the patient, the case had a short-term follow up so further clinical evaluations should must be performed for an exact evidence on the matter. Overall, it was found that when dealing with children, the implants placed should be of a smaller size as a result of their smaller sized maxillary and cortical bones [27] .…”
Section: Studies On General Outcomementioning
confidence: 99%